A mus-51 RIP allele for transformation of Neurospora crassa - Zachary J. Smith; Stacy Bedore; Stephanie Spingler; Thomas M. Hammond (Fungal Genetics Reports, 2016)
This report describes the construction and characterization of mus-51RIP70, an allele for high-efficiency targeted integration of transgenes into the genome of the model eukaryote Neurospora crassa. Two of the mus-51RIP70 strains investigated in this work (RZS27.10 and RZS27.18) can be obtained from the Fungal Genetics Stock Center. The two deposited strains are, to our knowledge, genetically identical and neither one is preferred over the other for use in Neurospora research.